Disconjugacy of Eye Movements during Attempted Fixation: A Sufficient Marker for Amblyopia? - Irsch, Kristina; Guyton, David L.; Geary, Robert B.; Tian, Jing; Gramatikov, Boris I.; Ying, Howard S. (Klinische Monatsblätter für Augenheilkunde, 2022)
Background To investigate whether detection of disconjugacy of eye movements during attempted fixation, or interocular position instability, may serve as a single sensitive test for amblyopia.Patients/Methods and Material Binocular eye movements were recorded at 500 Hz using the EyeLink 1000 eye tracker (SR Research Ltd., Kanata, Ontario, Canada) and analyzed using EyeLink software and Matlab (MathWorks, Natick, MA, USA). Eight subjects (four amblyopes, one successfully treated amblyope, and three non-amblyopes: 7 – 44 years) were asked to fixate on a stationary cross subtending 0.5° at 57 cm. Interocular position instability was quantified by calculating the minimum area bivariate contour ellipse (BCEA) encompassing 68% of the difference between right and left eye position points during 20-second viewing epochs. For statistical analysis, BCEA values, as well as visual acuity and stereoacuity, were normalized by base-10 logarithm transformation.Results The amblyopic subjects with persistent vision loss (one anisometropic, two strabismic, one deprivation; uncorrected visual acuity range 20/60 – 20/300, corrected stereoacuity range nil-400 arcsec) showed significantly higher interocular position instability (larger 68% BCEAs) than the non-amblyopic subjects (uncorrected visual acuity range 20/20 – 20/800, corrected stereoacuities of 20 arcsec) and the successfully treated strabismic amblyope (to the 20/20 level of visual acuity and 70 arcsec of stereoacuity) during binocular viewing trials; p < 0.01. Interocular position stability was strongly correlated with stereoacuity (in that better stereoacuity was associated with lower 68% BCEAs; r = 0.95), but not with visual acuity (r = 0.20).Conclusion Interocular position instability appears to differentiate amblyopic from non-amblyopic subjects and appears to improve after successful treatment. Interocular position instability may therefore prove to be a single sensitive test for the presence of amblyopia. As a difference measure, it is inherently less susceptible to head motion and calibration error, as well as to conjugate eye motion, and as such is expected to be somewhat immune to latent nystagmus. Interocular position instability may also be useful to guide treatment, especially in preverbal children, and to assess the efficacy of novel treatments. Further research is required to establish optimal interocular position instability thresholds and to determine how specific this measure is to amblyopia.
Keywords: amblyopia; pediatric vision screening; fixational eye movements; interocular position instability; disconjugacy of eye movements